Potensi dan Pemanfaatan Tanaman Obat Keluarga (TOGA) Studi Kasus: Desa Tarumajaya RW 07 RT 02, Kecamatan Kertasari, Kabupaten Bandung - Aditya Zhafari Nur Itmam; Kartika Sari; Aldy Permana Ramdhani; Aliftiyah Aura Rosyda; Damiyana Permatasari; Dinda Amalia Nurjanah; Mochammad Faizal Alfarizky; Nilam Wulansari; Risma Nur Arifah; Sayyidah Fatimah Azzahra; Sahnaz Ramadhani; Sinta Sukmawati (Pusat Riset dan Inovasi Nasional, 2025)
The Community Service Program (KKN) in Tarumajaya Village, Kertasari District, focused on the use of Family Medicinal Plants (TOGA) as an effort to improve community health independence. Limited access to formal health facilities is the background to the importance of introducing Family Medicinal Plants (TOGA) as an alternative natural treatment. The goal of this program is to increase community knowledge and skills in cultivating and utilizing Family Medicinal Plants (TOGA) for daily health needs. The methods used are education on the benefits and processing of medicinal plants, as well as direct planting practices in the community environment. This activity was attended by 25 residents and succeeded in planting 5 types of plants and 85 polybags consisting of red ginger (Zingiber officinale L.), fig tree (Ficus carica L.), moringa (Moringa oleifera L.), cat's whiskers (Orthosiphon aristatus L.), and aloe vera (Aloe vera L.). The results showed very good community participation and increased understanding, evidenced by the start of independent planting of Family Medicinal Plants (TOGA) in their respective yards. This program has succeeded in increasing public awareness that Family Medicinal Plants (TOGA) are not only useful as a